Heart and Sports Detraining in Water Polo Athletes - Armando Marín Rojas; Jorge Luis Abreus Mora (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
The balance of the heart in athletes favors morphological and functional stability that favors cardiovascular function parameters within normal ranges, manifested in adequate values of: systolic and diastolic blood pressure, heart rate, respiratory rate and physical fitness for training and daily activities. Due to the biological sacrifices that this implies, retired water polo athletes suffer from cardiovascular morphofunctional adaptations that must be addressed when they accept retirement and move on to sports detraining, which constitutes a prophylactic and therapeutic strategy for the health care of athletes. Early interventions are proposed, with aerobic work schedules, to balance cardiovascular morphofunctional adaptations in retired high-performance athletes.